Structural and logical analysis of a comprehensive hedgehog signaling pathway to identify alternative drug targets for glioma, colon and pancreatic cancer - Chowdhury, Saikat; Pradhan, Rachana N.; Sarkar, Ram Rup (Plos One, 2013)
Hedgehog is an evolutionarily conserved developmental pathway, widely implicated in controlling various cellular responses such as cellular proliferation and stem cell renewal in human and other organisms, through external stimuli. Aberrant activation of this pathway in human adult stem cell line may cause different types of cancers. Hence, targeting this pathway in cancer therapy has become indispensable, but the non availability of detailed molecular interactions, complex regulations by extra- and intra-cellular proteins and cross talks with other pathways pose a serious challenge to get a coherent understanding of this signaling pathway for making therapeutic strategy. This motivated us to perform a computational study of the pathway and to identify probable drug targets. In this work, from available databases and literature, we reconstructed a complete hedgehog pathway which reports the largest number of molecules and interactions to date. Using recently developed computational techniques, we further performed structural and logical analysis of this pathway. In structural analysis, the connectivity and centrality parameters were calculated to identify the important proteins from the network. To capture the regulations of the molecules, we developed a master Boolean model of all the interactions between the proteins and created different cancer scenarios, such as Glioma, Colon and Pancreatic. We performed perturbation analysis on these cancer conditions to identify the important and minimal combinations of proteins that can be used as drug targets. From our study we observed the under expressions of various oncoproteins in Hedgehog pathway while perturbing at a time the combinations of the proteins GLI1, GLI2 and SMO in Glioma; SMO, HFU, ULK3 and RAS in Colon cancer; SMO, HFU, ULK3, RAS and ERK12 in Pancreatic cancer. This reconstructed Hedgehog signaling pathway and the computational analysis for identifying new combinatory drug targets will be useful for future in-vitro and in-vivo analysis to control different cancers.

Structural insight of NICD-MAML interactions: virtual screening, docking and molecular dynamics study for the identification of potential inhibitor - Sinha, Noopur; Chowdhury, Saikat; Sarkar, Ram Rup (Letters in Drug Design & Discovery, 2016)
Activation of Notch signalling pathway is triggered by binding of NICD to transcription factor CSL and transcriptional co-activator MAML, which involves in various biological functions as well as progression of diseases. Recent prediction shows suppression of cancer causing genes of this pathway through inhibition of NICD-MAML interaction. Through virtual screening against ``NCI Diversity 3'' of Zinc database, we identified a potential inhibitor ``ZINC01690699'' (1-N,4-N-bis[3-(1H-benzimidazol-2-yl)phenyl]benzene-1,4-dicarboxamide; 1-N, 4-dicarboxamide) possessing highest binding affinity to block the two distinct Binding Sites of NICD to inhibit NICD-MAML interaction and also found the most imperative and essential Binding Site (Site I). Inhibition of this interaction caused by binding of ZINC01690699 is validated by protein-protein docking and the prolonged binding as well as stability of NICD-Inhibitor complex is supported by molecular dynamics simulation. The study not only identifies the best inhibitor but also proposes a potential drug for the treatment of cancers.
Keywords: free energy of binding; MAML; NICD; Notch signalling; potential inhibitor; ZINC01690699

Study of combinatorial drug synergy of novel acridone derivatives with temozolomide using in-silico and in-vitro methods in the treatment of drug-resistant glioma - Chakravarty, Malobika; Ganguli, Piyali; Murahari, Manikanta; Sarkar, Ram Rup; Peters, Godefridus Johannes; Mayur, Y. C. (Frontiers in Oncology, 2021)
Drug resistance is one of the critical challenges faced in the treatment of Glioma. There are only limited drugs available in the treatment of Glioma and among them Temozolomide (TMZ) has shown some effectiveness in treating Glioma patients, however, the rate of recovery remains poor due to the inability of this drug to act on the drug resistant tumor sub-populations. Hence, in this study three novel Acridone derivative drugs AC2, AC7, and AC26 have been proposed. These molecules when combined with TMZ show major tumor cytotoxicity that is effective in suppressing growth of cancer cells in both drug sensitive and resistant sub-populations of a tumor. In this study a novel mathematical model has been developed to explore the various drug combinations that may be useful for the treatment of resistant Glioma and show that the combinations of TMZ and Acridone derivatives have a synergistic effect. Also, acute toxicity studies of all three acridone derivatives were carried out for 14 days and were found safe for oral administration of 400 mg/kg body weight on albino Wistar rats. Molecular Docking studies of acridone derivatives with P-glycoprotein (P-gp), multiple resistant protein (MRP), and O6-methylguanine-DNA methyltransferase (MGMT) revealed different binding affinities to the transporters contributing to drug resistance. It is observed that while the Acridone derivatives bind with these drug resistance causing proteins, the TMZ can produce its cytotoxicity at a much lower concentration leading to the synergistic effect. The in silico analysis corroborate well with our experimental findings using TMZ resistant (T-98) and drug sensitive (U-87) Glioma cell lines and we propose three novel drug combinations (TMZ with AC2, AC7, and AC26) and dosages that show high synergy, high selectivity and low collateral toxicity for the use in the treatment of drug resistant Glioma, which could be future drugs in the treatment of Glioblastoma.
Keywords: acridone derivatives; drug combinations; drug resistance; Glioma; mathematical model; synergy index